Exploring the link among entry characteristics, participation behaviors and course outcomes of online learners: An examination of learner profile using cluster analysis. (9th July 2012) - Yukselturk, Erman; Top, Ercan
Abstract: Online learner profiles have diversified such that now, they include all types of participants from a variety of backgrounds. This study analyzed online learner profiles in regard to their entry characteristics, participation behaviors and achievement of course outcomes. The sample consisted of 186 participants from an online course that required the employment of synchronous and asynchronous communication methods over the Internet. The data were collected through five online questionnaires and included 10 variables (gender, age, work status, self‐efficacy, online readiness, self‐regulation, participation in discussion list, participation in chat sessions, satisfaction and achievement). A two‐step cluster analysis, chi‐square analysis and multivariate analysis were used to analyze the collected data. The results indicated that online learners fell into three significantly different clusters and within each cluster, learners had a close combination of employment characteristics, gender type, age level, perception of self‐efficacy for online technologies and participation behavior level.